Publication of Armenian folk songs by Ghevond Alishan - Vardanyan, Nvard (Bulletin of Yerevan University B: Philology, 2021)
The article examines the folk songs published by Ghevond Alishan. The history of the publication of songs on the pages of "Bazmavep" during 1843-1850 is presented. Various issues related to the basic principle of the classification of songs called "ramkakan", which means folk songs, are being studied. Despite the content, not all of the songs in the collection are folk songs, there are also literature and author’s songs. It is clear that for Alishan, the key was the presence of the nationality of the language and style of songs. We find the same approach in "Songs of Nahapet", a folk singer invented by Alishan. In the article, an attempt is made to deffer folk and author’s songs in the collection "Armenian folk songs" by Alishan, the types of folk songs are presented, their further destinies are studied. It briefly talks about the influence of folk songs published in Alishan’s collection on Armenian literature, in particular in the poems of Hovhannes Tumanyan.